Classification of Ultrasonic Action Effects on Ceramic Powders being compacted; Physics and Chemistry of Ultra-Disperced (Nano-)Systems - Khasanov O. L. Oleg Leonidovich; Dvilis E. S.; Sokolov V. M.; Pokholkov Y. P. Yuri Petrovich; Dedov N. V. (2002, 2002)
В фонде НТБ ТПУ отсутствует